Kierkegaard’s Repetitions: A Rhetorical Reading of Søren Kierkegaard’s Concept of Repetition - Holm, Isak Winkel (KIERKEGAARDIANA, 1991)
Kierkegaard’s Repetitions: A Rhetorical Reading of Søren Kierkegaard’s Concept of Repetition